A novel CSTR-type of hollow fiber membrane biofilm reactor for consecutive nitrification and denitrification - Shin, Jeong-Hoon; Sang, Byoung-In; Chung, Yun-Chul; Choung, Youn-Kyoo (ELSEVIER SCIENCE BV, 2008)
A continuous stirred tank reactor (CSTR) type of hollow fiber membrane biofilm reactor (HF-MBfR) using composite membranes was investigated for the nitrogen removal in synthetic wastewater. The CSTR-type of HF-MBfR process couples autotrophic biological nitrogen removal reactors with the bubbleless mass transfer of oxygen and hydrogen through hollow fiber membranes. For nitrification, CSTR-type of HF-MBfR was operated over 400 days and for hydrogenotrophic denitrification, CSTR-type of HF-MBfR was operated over 300 days. The maximum steady-state NH4+-N removal rate achieved was 0.25 kg N/m(3) day (2.06 g N/m(2) day) and the denitrification rate achieved was 0.22 kg N/m(3) day (1.72 g N/m(2) day). Consequently, in the HF-MBfRs, biofilms were formed stably on surface of membranes, and nitrification and hydrogenotrophic denitrification were performed successfully during long-term operation.
Keywords: WATER; BIOREACTOR